Employee Performance Optimization - Ira Silvia Nasution, Rizky; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This study aims to seeThe Influence of Organizational Culture and Job Satisfaction on Employee Performance with Job Stress as a Mediating Variable at BPJS Ketenagakerjaan Branch Offices throughout Medan Raya. This type of research uses a quantitative method, this research was conducted at BPJS Ketenagakerjaan Branch Offices throughout Medan Raya, the population used was 80 employees consisting of Medan City as many as 20 personnel, Medan Utara as many as 20 personnel, Tanjung Morawa as many as 20 personnel and Binjai as many as 20 personnel. The sample used was all populations of 80 employees with saturated samples as the sampling technique. The data sources used were primary data sources and data collection by distributing questionnaires. This research model uses phat analysis and the measuring instrument is the smart PLS application version 3.3.3. The results of this study are as follows: Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.285 and p values 0.045. Organizational Culture has a positive and significant effect on Job Stress with an original sample value of 0.628 and P values 0.000. Job satisfaction has a positive and significant effect on employee performance with an original sample value of 0.492 and p values of 0.000. Job satisfaction has a positive and significant effect on Job Stress with an original sample value of 0.281 and p values of 0.007. Job Stress has a positive and insignificant effect on employee performance with an original sample value of 0.191 and p values of 0.149. Organizational Culture has a positive and insignificant effect on employee performance through work stress indirectly with an original sample result of 0.120 and p values of 0.165. Job satisfaction has a positive and insignificant effect on employee performance through work stress with an original sample value of 0.054 and p values of 0.234.